Exploiting fitness distance correlation (FDC) of timetabling instances - Md Sultan, Abu Bakar; Mahmod, Ramlan; Sulaiman, Md Nasir; Abu Bakar, Mohd Rizam (2005)
The Timetabling Problem is a combinatorial optimization problem. The University Course Timetabling Problems (UCTP) deal with the scheduling of the teaching program. In this paper we analyze the performance of Hybrid Evolutionary Metaheuristic for a set of timetabling instances benchmark through an analysis of the fitness-distance correlation (FDC) . FDC is a statistical measure of a search difficulty in relation to genetic algorithm. We propose new ways of FDC analysis. Initial result indicates that FDC can also be used in different ways of analysis as well as different problem instances.